Caesalpinia mexicana Mexican Caesalpinia: FPS82/FP082, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed description of the Mexican caesalpinia (Caesalpinia mexicana), a small tree or large shrub known for its fine-textured foliage and bright yellow flowers. It outlines the plant’s characteristics, including its moderate growth rate, evergreen leaves, and drought tolerance. The document also discusses its potential uses in landscaping, such as near patios, in parking lot islands, or as a container plant. Additionally, it highlights the plant’s adaptability to various soil types and its general pest resistance. The Mexican caesalpinia is noted for its ornamental value and suitability for tough planting sites. Original publication date October 1999.